Temporal Inferences in Conversation - Paul, Christine (Research in Language, 2011)
Within this article, I explore how coproductions (expansions made by a second speaker upon a previous utterance) and questions regarding prior utterances work to verbalize inferences regarding the temporal information in spoken German conversation. While questions regarding prior utterances and coproductions are traditionally understood to have different communicative functions (signaling understanding/ misunderstanding; turn taking) to coproductions, empirical data shows how these expression types enable the speaker to gradually verbalize different strengths of assumption about details of the previous turn. These two expression types are not a dichotomy, but a continuum.